Interpretation of Mud Losses in Carbonates Based on Cuttings Description, Well-Logging, Seismic and Coherency Data - Bashara, Zainab R.; A. Hadi, Farqad; Kasing, Martin (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
Hartha Formation is an overburdened horizon in the X-oilfield which generates a lot of Non-Productive Time (NPT) associated with drilling mud losses. This study has been conducted to investigate the loss events in this formation as well as to provide geological interpretations based on datasets from nine wells in this field of interest. The interpretation was based on different analyses including wireline logs, cuttings descriptions, image logs, and analog data. Seismic and coherency data were also used to formulate the geological interpretations and calibrate that with the loss events of the Hartha Fm.   The results revealed that the upper part of the Hartha Fm. was identified as an interval capable of creating potential mud losses, resulting in high NPT. This is due to its diagenetic features such as succrosic dolomites and vuggy zones that could act as thief zones. Seismic potential was used for the prediction of the geological related non-productive drilling time in the Hartha interval. The seismic data quality in this interval was good, with geological observations already made. Detailed interpretation and analysis of the Hartha interval were performed and integrated with the existing seismic interpretation, rock properties, and NPT database to calibrate wells with the loss events to the seismic observations.